Attachment of Cell-Binding Ligands to Arginine-Rich Cell-Penetrating Peptides Enables Cytosolic Translocation of Complexed siRNA. Issue 1 (22nd January 2015) - Zeller, Skye; Choi, Chang Seon; Uchil, Pradeep D.; Ban, Hong-Seok; Siefert, Alyssa; Fahmy, Tarek M.; Mothes, Walther; Lee, Sang-Kyung; Kumar, Priti
Summary Cell-penetrating peptides (CPPs), such as nona-arginine (9R), poorly translocate siRNA into cells. Our studies demonstrate that attaching 9R to ligands that bind cell surface receptors quantitatively increases siRNA uptake and importantly, allows functional delivery of complexed siRNA. The mechanism involved accumulation of ligand-9R:siRNA microparticles on the cell membrane, which induced transient membrane inversion at the site of ligand-9R binding and rapid siRNA translocation into the cytoplasm. siRNA release also occurred late after endocytosis when the ligand was attached to the L isoform of 9R, but not the protease-resistant 9DR, prolonging mRNA knockdown. This critically depended on endosomal proteolytic activity, implying that partial CPP degradation is required for endosome-to-cytosol translocation. The data demonstrate that ligand attachment renders simple polycationic CPPs effective for siRNA delivery by restoring their intrinsic property of translocation.